Emerging Issues Questioning the Current Treatment Strategies for Lumbar Disc Herniation - Wan, Zhong Y.; Shan, Hua; Liu, Tang F.; Song, Fang; Zhang, Jun; Liu, Zhi H.; Ma, Kun L.; Wang, Hai Q. (Frontiers in Surgery, 2022)
Lumbar disc herniation is among the common phenotypes of degenerative lumbar spine diseases, significantly affecting patients’ quality of life. The practice pattern is diverse. Choosing conservative measures or surgical treatments is still controversial in some areas. For those who have failed conservative treatment, surgery with or without instrumentation is recommended, causing significant expenditures and frustrating complications, that should not be ignored. In the article, we performed a literature review and summarized the evidence by subheadings to unravel the cons of surgical intervention for lumbar disc herniation. There are tetrad critical issues about surgical treatment of lumbar disc herniation, i.e., favorable natural history, insufficient evidence in a recommendation of fusion surgery for patients, metallosis, and implant removal. Firstly, accumulating evidence reveals immune privilege and auto-immunity hallmarks of human lumbar discs within the closed niche. Progenitor cells within human discs further expand the capacity with the endogenous repair. Clinical watchful follow-up studies with repeated diagnostic imaging reveal spontaneous resolution for lumbar disc herniation, even calcified tissues. Secondly, emerging evidence indicates long-term complications of lumbar fusion, such as adjacent segment disease, pseudarthrosis, implant failure, and sagittal spinal imbalance, which get increasing attention. Thirdly, systemic and local reactions (metallosis) for metal instrumentation have been noted with long-term health concerns and toxicity. Fourthly, the indications and timing for spinal implant removal have not reached a consensus. Other challenging issues include postoperative lumbar stiffness. The review provided evidence from a negative perspective for surgeons and patients who attempt to choose surgical treatment. Collectively, the emerging underlying evidence questions the benefits of traditional surgery for patients with lumbar disc herniation. Therefore, the long-term effects of surgery should be closely observed. Surgical decisions should be made prudently for each patient.